PENGETAHUAN PESERTA PROGRAM PENDIDIKAN DOKTER SPESIALIS NEUROLOGI INDONESIA TENTANG SEMIOLOGI BANGKITAN EPILEPSI - Suryani Gunadharma,* Yovita Stevina,* Anam Ong,* Siti Aminah,* Lisda Amalia,* Uni Gamayani* (NEURONA, 2020)
INTRODUCTION SEIZURE SEMIOLOGY IS AN EFFECTIVE METHOD FOR SYNDROME DIAGNOSIS ESPECIALLY WHEN ELECTROENCEPHALOGRAM EEG AND BRAIN MAGNETIC RESONANCE IMAGING MRI CANNOT PROVIDE SUFFICIENT INFORMATION DIAGNOSIS OF CLINICAL EPILEPSY BASED ON SEMIOLOGY REQUIRED A COMPREHENSIVE KNOWLEDGE ESPECIALLY FOR NEUROLOGY RESIDENTS AS CANDIDATE OF NEUROLOGY SPECIALIST